Analisis Dampak Penerapan Program Keluarga Harapan bagi Kesejahteraan Masyarakat Kelurahan Tegal Sari Mandala Medan - Mutia Harahap; Bahrum Jamil; Marlina Deliana (Universitas Medan Area, 2023)
The Family Hope Program (PKH) is a conditional social assistance provided to Very Poor Households (RTSM) in improving welfare through education and health. This study aims to analyze the impact of the implementation of PKH on the welfare of the community in the Tegal Sari Mandala II village. The research method uses qualitative methods. Data collection techniques using interviews, observation and documentation. The results of the study show that the impact of the implementation of PKH on the welfare of the people of Tegal Sari Mandala II Village is that before the existence of PKH it can be said that it is not yet prosperous and is still under welfare because it is still very vulnerable in the fields of education and health. Second, the extent to which the impact of PKH in Tegal Sari Mandala II has a very good impact and is very useful for the recipients. However, the people who have not been targeted are still classified as not prosperous. These three PKH goals have had a very good effect or impact on people's welfare and the target community for PKH assistance recipients come from underprivileged families. And the supporting factors for the implementation of PKH so that it has an impact on increasing family welfare, namely the role of PKH facilitators in providing assistance so that they can achieve the desired goals and the participation of beneficiary families can be seen from their active participation in the P2K2 program which aims to increase knowledge and awareness of beneficiary families.